Production of power using underground coal gasification. Issue 24 (16th December 2016) - Doucet, Denis; Perkins, Greg; Ulbrich, Andreas; du Toit, Ernest
ABSTRACT: Underground coal gasification (UCG) is a process that converts deep, un-mineable coal resources into syngas, which can then be converted into valuable end products such as electric power. This paper provides a summary of the options to combine UCG with electric power production and focuses on commercial-scale applications using a combined-cycle power plant including integration options and syngas cleanup steps. Simulation results for a UCG power plant with carbon capture are compared against the results for an equivalent Integrated Gasification Combined Cycle (IGCC) plant using the same feedstock. Relative capital cost savings for a UCG power plant are estimated based on published IGCC process unit costs. The UCG power plant with carbon capture is shown to provide a higher thermal efficiency, lower CO2 intensity, and lower capital cost than an equivalent IGCC plant. Finally, the potential of UCG as a method for producing cost-effective, low-emissions electrical power from deep coal is discussed and some of the challenges and opportunities are summarized.